Exploring caregiver challenges, digital health technologies, and healthcare support: a qualitative study - Zainal, Humairah; Xiaohui, Xin; Thumboo, Julian; Seah, Siang Joo; Leng, Low Lian; Kok Yong, Fong (Frontiers in Digital Health, 2025)
IntroductionInformal caregiving often involves navigating complex healthcare tasks, a challenge that is amplified by the growing burden of chronic diseases and an ageing population. Digital health technologies (DHTs)—including mobile health apps, wearable devices, and telemedicine platforms—offer potential support, yet their integration into caregiving remains underexplored. This study investigates the challenges caregivers face when using DHTs in Singapore and identifies resources needed to optimize their use in everyday caregiving.MethodsThirty informal caregivers of adults with chronic illnesses and/or physical or cognitive impairments were recruited through purposive sampling via caregiver and personal networks, and community organizations. Semi-structured interviews were conducted, and thematic analysis was used to identify key barriers and potential solutions.ResultsCaregivers reported using DHTs such as the HealthHub app, Fitbit wearables, and video teleconsultation services. Seven key challenges emerged: (1) lack of formal training in DHT use, (2) difficulties providing timely care, (3) limitations of teleconsultations for complex needs, (4) poor app usability, (5) cost concerns, (6) age-related digital literacy gaps, and (7) cultural tensions in adopting DHTs. Solutions proposed included caregiver-targeted training programs, streamlined digital access to care, improved DHT design, equitable access to DHTs, age-inclusive healthcare services, affordability schemes, and culturally sensitive support.DiscussionThis study highlights significant barriers to DHT adoption among informal caregivers and offers practical strategies to improve their use. Addressing these challenges through training, inclusive design, and equitable access can enhance caregiver resilience and system sustainability in digital health integration.